SEBUAH BEBAN RELIGIUS: Tradisi Makan Bersama Dalam Ibadah Pada Komunitas Kristen Dari Perspektif Perempuan Miskin - Tibinge, Nada; Mosooli, Ermin Alperiana; Lembolangi, Lefrand (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2024)
The tradition of providing meals during worship is part of a religious culture aimed at strengthening social relationships and expressing gratitude to God. However, for impoverished women, this tradition can become a financial and emotional burden. This study aims to examine the negative impacts of this tradition, particularly on women facing economic challenges, with a focus on the cultural, religious, and social pressures they experience. The research was conducted in Jemaat Batu Karang Ombuli, a local church in Banggai Kepulauan Regency, Central Sulawesi Province. The study employed a quantitative method with a survey approach involving 95 female respondents. The results show that respondents experience significant pressure. Most respondents (average score: 3.27) agreed that communal meals are an entrenched tradition, making them feel obligated to participate. Additionally, shared meals are understood as an expression of gratitude to God (average score: 3.47), even though financial constraints often pose challenges. Social pressure was also felt quite strongly (average score: 2.93), with a sense of shame being prevalent when respondents fail to provide meals. This study highlights that a tradition intended to foster solidarity instead creates burdens for vulnerable groups. Recommendations are provided for the church to develop more inclusive practices, emphasizing voluntary participation and solidarity without financial pressures, to preserve genuine values of togetherness.